Análise molecular de amostras negativas para o antígeno específico da próstata (PSA) coletadas de vítimas de crimes sexuais - Ruiz, Karine Pequeno Nakao (2017)
The finding of sperm through the screening tests on samples collected from rape victims confirms the occurrence of the sexual act, but its absence usually closes biological research in the crime in question, leaving a gap about the authorship of the crime, as well as about the criminal typification. The present work aimed to analyze the need of implementation in forensic routine of Genetics Laboratories of molecular analysis of negative samples to the prostate-specific antigen (PSA) collected from sex crimes victims. Vaginal swabs were selected and proceedings collected from 200 women who have been victims of those crimes in Paraíba from January 2015 to January 2016. Such materials had been sorted and presented negative result for PSA. Proceeded to the sample quantification by Real-time PCR using the Plexor® HY kit and there was a far greater concentration of autosomal DNA in relation to the male DNA. With the use of thermal cyclers GeneAmp® PCR System 9700, 200 DNA samples extracted from the sperm fraction (SF) were amplified for Y-STR with the use of PowerPlex® Y23 Systems and AmpFlSTR® Yfiler PCR Amplification kits. Such products have been subjected to capillary electrophoresis in genetic sequencer ABI PRISM™ 3500 Genetic Analyzer and the results analyzed by GeneMapper® ID software v 3.2. The fractions analyzed, only two full profiles amplification (1%), 24 (12%) partials, while the 174 remaining samples (87%) did not present any amplification. Screening with PSA testing negative served, statistically, how to determine guiding absence of sperm in swabs of vaginal origin and anally for victims of sex crimes. However, in this study were analyzed samples from rape victims. Due to the large social call caused by this type of crime, any nonzero statistic must be acceptable to a presumptive test. The results obtained have awakened to the need to study a new way of sorting this material, as well as the repetition of some analytical steps in order to get a genetic profile informative for illicit criminal resolution.